Technology: Role in Maternal and Infant Mortality Ratios. Midwives and Nurses Perception in Cameroon-West Africa. A Cross-sectional Quantitative Survey. - Pivadga, Collins; Ekpah , Daniel (Student’s Journal of Health Research Africa, 2022)
Background: Glocal efforts to curb the maternal/infant mortality ratio have not reached a satisfactory level with Sub-Saharan countries accounting for 86% (25400) of the global maternal death in 2017. However, technology has enhanced prompt management of preventable maternal/infant deaths via remote obstetric consultations/care along the whole continuum of pregnancy, childbirth, and postnatal care. Aim: The survey aimed at assessing midwives’ and nurses’ perceptions on the role of tele-obstetrics in improving maternal/infant mortality in Africa and the significance of educational qualification and years of work experience on perception. Methodology; The survey employed quantitative and non-probability convenient sampling techniques to select 138 midwives and nurses. Data collection tool was used to collect data in two phases; phase-I as web-base (22nd-28th February 2021) and phase II, self-administered (1st-5th March 2021) using questionnaire then descriptive and inferential statistics were computed at 95% Confidence Interval on Statistical Package for Social Sciences version 20 and presented in the form of tables, pie charts, and bar charts. Results: The respondent rate was 86% (118/138), and at a mean score of 1.31(0.043)±0.466, 68.6% (81/118) of participants perceived tele-obstetrics vital to curb maternal/infant mortality. Among those with positive perception, 43.2%(35/81) [chi-2=6.3(33.3%)0.27] had a bachelor of science in midwifery/nursing. Within those with ≤5years of experience, 74.6%(47/63) [chi2=4.9(37.5%)0.17] supported technological application in midwifery care. Conclusion: Midwives and nurses recognize tele-obstetrics capable of improving maternal/infant health, and this recognition is not so different amongst the different cadre of Midwives/Nurses although those with few years of work experience support tele-obstetrics than those with many years of work experience. Recommendation: It is recommended for all United Nations member states to create a platform that encourages the implementation of tele-obstetric systems in all healthcare settings and midwifery curriculum as midwives and nurses will be willing to improve care via the use of technology.